A simulation of the Cerro Hudson SO2 cloud - Schoeberl, Mark R.; Doiron, Scott D.; Lait, Leslie R.; Newman, Paul A.; Krueger, Arlin J. (1993)
An isentropic trajectory model is used to simulate the evolution of the southern hemisphere SO2 cloud associated with the eruption of Cerro Hudson. By matching the parcel trajectories with total ozone mapping spectrometer SO2 retrievals, the principal stratospheric injection region is determined to be between 11 and 16 km in altitude. This region is characterized by weak wind shears and is located just poleward of the subtropical jet in the outer fringe of the stratospheric polar vortex. The lack of wind shear in the injection region explains the slow zonal dispersal of the SO2 cloud which was still clearly observed 19 days after the eruption. The trajectory model simulation of the SO2 cloud shows good agreement with observations for 7 days after the eruption. Using the potential vorticity and potential temperature estimates of the initial eruption cloud, the cloud position relative to the polar night jet is shown to be nearly fixed up to September 2, 1991, which was as long as the cloud was observed. This result suggests that the lower stratospheric polar and midlatitude regions are nearly isolated from each other during the late August period.